Access to the Green Economy through Anaerobic Digestion: A Siting Study. - Aiu, Imaikalani.; Bahirwani, Suveer.; Farnham, Abby.; Parisi, Anthony. (Tufts University. Tisch Library., 2018)
2014 M.A. in Urban and Environmental Policy and Planning Field Project. Client: Cooperative Energy, Recycling & Organics/Cooperativa Para Energía, Reciclaje & Organicos. This project is part of the Office of Sustainability Student Project Database, a place to share and view student projects related to sustainability and the environment.